The Atmospheric Circulation Reconstructions over the Earth (ACRE) initiative ACRE China workshop: Recovery, digitization, and analysis of pre‐mid‐twentieth century climate observational data in East Asia workshop on 23–24 August, Beijing, China. Issue 1 (10th January 2017) - Williamson, F.; Ren, Guoyu; Allan, Rob
Abstract: This commentary discusses a recent workshop designed to explore the extant historic instrumental record of weather observations for China, East Asia, and the China Seas region; to uncover new sources of observations; and to work on joint initiatives for their recovery and inclusion in open access data sets. The workshop was funded by the UK Newton Fund's Climate Science for Service Partnership China. It was organized by the Atmospheric Circulation Reconstructions over the Earth China, the China Meteorological Administration (CMA), the Beijing Climate Centre, and the China University of Geosciences (Wuhan) and held at CMA offices in Beijing. Key Points: This is a commentary on a recent China/UK collaborative workshop held 23–24 August 2016 The workshop was held for the purpose of facilitating historic instrumental observations for the China/China Seas region The workshop has resulted in better knowledge sharing and agreements for future data recovery work (DARE) to facilitate climate reanalyses